2021
DOI: 10.3389/fimmu.2021.685139
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Immunological Changes Appearing in the CSF During the Early Immunosenescence Process Occurring in Multiple Sclerosis

Abstract: Patients with multiple sclerosis (MS) suffer with age an early immunosenescence process, which influence the treatment response and increase the risk of infections. We explored whether lipid-specific oligoclonal IgM bands (LS-OCMB) associated with highly inflammatory MS modify the immunological profile induced by age in MS. This cross-sectional study included 263 MS patients who were classified according to the presence (M+, n=72) and absence (M-, n=191) of LS-OCMB. CSF cellular subsets and molecules implicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Although previous studies point out that premature immunosenescence affects patients with auto- immune diseases, most do not propose a reference age. However, a recent publication [ 33 ] study this phenomenon classifying the 263 MS patients according to their age in subgroups of five years (i.e., ≤25, 26–30, 31–35 years, and so on). Eventually, these authors sorted patients into two groups: age ≤45 or > 45 years because the most significant changes in CSF lymphocyte numbers among M− patients were observed at this age, 45 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies point out that premature immunosenescence affects patients with auto- immune diseases, most do not propose a reference age. However, a recent publication [ 33 ] study this phenomenon classifying the 263 MS patients according to their age in subgroups of five years (i.e., ≤25, 26–30, 31–35 years, and so on). Eventually, these authors sorted patients into two groups: age ≤45 or > 45 years because the most significant changes in CSF lymphocyte numbers among M− patients were observed at this age, 45 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, these authors sorted patients into two groups: age ≤45 or > 45 years because the most significant changes in CSF lymphocyte numbers among M− patients were observed at this age, 45 years old. The authors observed that the main effect of aging in M− was a decrease in the absolute numbers of CSF T cells (including Th1 and Th17 cells) and B cells (including TNF-alpha producers) with no augment of TIM−3 levels, being the only indication of immunosenescence a discrete increase of anti-CMV antibody titers [ 33 ]. By contrast, M+ patients show an age-associated increase of TIM−3, a biomarker of T cell exhaustion [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the possible impact of demographic, clinical, radiological, and genetic features on these relationships, the aforementioned process was repeated after stratifying the cohort accordingly, as well as considering baseline serological and viral load values (0 M). For continuous variables, the median values were selected as the cut-offs, except for age (the cut-off was 45 years old [ 19 ], proposed as the possible immunosenescence onset for MS patients) and EDSS (the cut-off was 3, proposed as the onset of irreversible disability [ 20 ]).…”
Section: Methodsmentioning
confidence: 99%
“…It is not clear how CMV and LSOCM interact. To what extent these differences are associated with more aggressive courses or with CMV can only be speculated [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…A pattern of premature immune aging has been demonstrated in the CD8 T cell compartment as well as in telomere length in leukocytes [ 28 , 31 ]. In MS patients, a moderate induction of T cell tolerance and activation of innate immunity with growing age seem to occur [ 30 ]. Both genetic factors, such as HLA DR4, and environmental factors, such as CMV infection, could accelerate immunosenescence in MS [ 27 , 35 ].…”
Section: Methodsmentioning
confidence: 99%